Thyroid Surgery in Children: Clinical Outcomes - Sinha, C. K.; Decoppi, Paolo; Pierro, Agostino; Brain, Caroline; Hindmarsh, Peter; Butler, Gary; Dattani, Mehul; Spoudeas, Helen; Kurzawinski, Tom R. (European Journal of Pediatric Surgery, 2015)
Aim The aim of this study was to review the outcomes of thyroid surgery in children operated for both benign and malignant conditions.Patients and Method Demography, clinical features, and surgical outcomes were noted retrospectively for operations performed during the last 23 years. Results were analyzed using Fisher exact test and Woolf (logit) method with p value < 0.05 considered as significant.Results In total, 61 children (43 girls and 18 boys) underwent thyroidectomy for benign (70%) and malignant (30%) conditions. Median follow-up period was 1.4 years. In the benign group, 84% children had Graves disease and 16% had other conditions. In this study, 42% children had total, 22% had near-total, 27% had subtotal, and 9% had type 2 hemithyroidectomy. In the malignant group, 50% had multiple endocrine neoplasia, 33% had papillary, 11% had follicular cancer, and 6% had B-cell lymphoma. Fifty percent children had prophylactic thyroidectomy, 44% had total thyroidectomy plus lymphadenectomy, and 6% had hemithyroidectomy. At the time of surgery, children with benign conditions were older than those with malignancy (median, 12 vs. 7.5 years). There were no incidents of postoperative bleeding or infection. Hypocalcemia was significantly more frequent in the malignant group (39 vs. 9%, p value = 0.01). The type of recurrent laryngeal nerve (RLN) injury was more serious in the benign group (one bilateral and one unilateral permanent injury) than in the malignant group (transient hoarseness in three). Overall rate of complications was higher for operations for malignancy (56 vs. 28%, p value = 0.07). In Graves disease, the subtotal thyroidectomies had a recurrence of 30% but no recurrence was seen following total or near-total thyroidectomy group (p value = 0.01). There was no recurrence in the malignant group. Children operated after 2000 were younger than those operated before 2000 (median age, 9 vs. 14 years). Malignant conditions were more common in children operated after 2000 in comparison to before 2000 (55 vs. 10%).Conclusion Benign conditions are commonest indications for thyroid surgery in children but the incidence of surgery for malignant conditions is rising. Overall rate of complications, especially hypocalcemia, is higher after surgery for malignancy but all cases of permanent RLN injury were in benign group. Total or near total thyroidectomy prevents recurrence of thyrotoxicosis and is an operation of choice for Graves disease.
Keywords: thyroid; surgery; children